The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1002/advs.202306305
|View full text |Cite
|
Sign up to set email alerts
|

Cocktail Cell‐Reprogrammed Hydrogel Microspheres Achieving Scarless Hair Follicle Regeneration

Shuaifei Ji,
Yingying Li,
Lei Xiang
et al.

Abstract: The scar repair inevitably causes damage of skin function and loss of skin appendages such as hair follicles (HF). It is of great challenge in wound repair that how to intervene in scar formation while simultaneously remodeling HF niche and inducing in situ HF regeneration. Here, chemical reprogramming techniques are used to identify a clinically chemical cocktail (Tideglusib and Tamibarotene) that can drive fibroblasts toward dermal papilla cell (DPC) fate. Considering the advantage of biomaterials in tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…By combining the liposome nanoparticles, photo-responsive hydrogel shell, microfluidic and photo-crosslinking techniques, the AHFS hydrogel/microspheres drug delivery system delivered sever small molecule drugs to fibroblasts and successfully in situ reprogramed them to dermal papilla cells (DPCs). The results of following experiments indicated that the AHFS system could activate the PI3K/AKT pathway, promoting wound healing and endogenous hair follicles regeneration, also could inhibit the transformation of fibroblasts to myofibroblasts and inhibit scar formation [ 256 ]. Biswas et al successfully delivered myoblast determination protein 1 (MYOD1) transcription factor in the cell nucleus of myoblast cells by PEG nanoparticle, and then reprogramed myoblast differentiation into skeletal, cardiac or smooth-muscle cells [ 257 ].…”
Section: Novel Techniques For Biomaterial-guided Wound Healingmentioning
confidence: 99%
“…By combining the liposome nanoparticles, photo-responsive hydrogel shell, microfluidic and photo-crosslinking techniques, the AHFS hydrogel/microspheres drug delivery system delivered sever small molecule drugs to fibroblasts and successfully in situ reprogramed them to dermal papilla cells (DPCs). The results of following experiments indicated that the AHFS system could activate the PI3K/AKT pathway, promoting wound healing and endogenous hair follicles regeneration, also could inhibit the transformation of fibroblasts to myofibroblasts and inhibit scar formation [ 256 ]. Biswas et al successfully delivered myoblast determination protein 1 (MYOD1) transcription factor in the cell nucleus of myoblast cells by PEG nanoparticle, and then reprogramed myoblast differentiation into skeletal, cardiac or smooth-muscle cells [ 257 ].…”
Section: Novel Techniques For Biomaterial-guided Wound Healingmentioning
confidence: 99%